Assessment of Development Results - Countries of the Organisation of Eastern Caribbean States & Barbados - United Nations Development Programme (United Nations, 2009)
The Assessment of Development Results (ADR) covered the sub-regional programme of the nine member countries of the Organisation of Eastern Caribbean States (OECS) and Barbados over the ongoing (2005-2009) and previous (2001-2004) programming cycles. The ADR notes that UNDP is working in a challenging and multifaceted development context, where relatively high levels of gross domestic product per capita and political stability occur side by side with considerable poverty, underemployment, gender and social inequities, institutional capacity weaknesses and vulnerability to risk, including extreme weather events. The publication concluded that although UNDP has undertaken a subregional programme with a strong profile and reputation it has achieved only moderate progress towards longer-term outcomes. It also found that the UNDP subregional programme had many commendable features and is respected by stakeholders and partners due to its consistent focus on improving human and social development in the Eastern Caribbean.